2022
DOI: 10.1007/s12325-022-02130-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Evolocumab in Adult Patients with Atherosclerotic Cardiovascular Disease in Canada

Abstract: Introduction To evaluate the cost-effectiveness of evolocumab when added to standard of care lipid-lowering treatment (LLT) for patients with atherosclerotic cardiovascular disease (ASCVD) who cannot adequately control their low-density lipoprotein cholesterol (LDL-C) despite optimized LLT in Canada. Methods An incremental cost-utility analysis was conducted using a Markov cohort state transition model adapted to the Canadian setting. Analyses were conducted from a publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Indeed, in patients with ACS whose LDL-C levels are not at threshold and have been treated with maximally tolerated statins and ezetimibe, ESC/EAS guidelines recommend intensification to PCSK9i in hospital if possible [7]. Some payer requirements (e.g., ezetimibe trial before prescription; LDL-C tests) may also contribute to the time delay between the AMI event and PCSK9i initiation [18][19][20]. The high number of ASCVD events observed before starting PCKS9i could reflect the study design, whereby pre-AMI events may be included if the LLT was initiated within 1 year of the AMI and events following LLT dispense were not captured.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in patients with ACS whose LDL-C levels are not at threshold and have been treated with maximally tolerated statins and ezetimibe, ESC/EAS guidelines recommend intensification to PCSK9i in hospital if possible [7]. Some payer requirements (e.g., ezetimibe trial before prescription; LDL-C tests) may also contribute to the time delay between the AMI event and PCSK9i initiation [18][19][20]. The high number of ASCVD events observed before starting PCKS9i could reflect the study design, whereby pre-AMI events may be included if the LLT was initiated within 1 year of the AMI and events following LLT dispense were not captured.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States found that the ICER for PCSK9 inhibitors compared to statins for preventing cardiovascular events is US$268,637 per QALY (in 2017), which is cost-effective (35). A similar conclusion reached Canada with the ICER being US$48,912 per QALY (in 2021) by adding PCSK9 inhibitors (36). However, with an ICER of US$133,613 per QALY (in 2019), PCSK9 inhibitors in China were far from costeffective when the decision threshold of three times of GDP (US $32,973 per QALY) (37).…”
Section: Discussionmentioning
confidence: 89%
“…The initiation of PCSK9i therapy can present a challenge to prescribing physicians, with more than 20% identifying cost/coverage issues as a barrier to starting this treatment. However, despite the cost of the drug, particularly in view of the significant benefits in reducing the need for coronary revascularization, MI, stroke, and death, PCSK9i therapy is cost-effective in high-risk secondary prevention settings, particularly in those with prior MI and persistent elevation of LDL-C despite optimal statin treatment [ 22 , 23 ]. Overall, these barriers to prescribing non-statin therapies shown in our study represented missed opportunities where additional lipid-lowering therapies were guideline-indicated.…”
Section: Discussionmentioning
confidence: 99%